Genotype–phenotype correlation in CC2D2A-related Joubert syndrome reveals an association with ventriculomegaly and seizures. Issue 2 (12th January 2012) - Bachmann-Gagescu, Ruxandra; Ishak, Gisele E; Dempsey, Jennifer C; Adkins, Jonathan; O'Day, Diana; Phelps, Ian G; Gunay-Aygun, Meral; Kline, Antonie D; Szczaluba, Krzysztof; Martorell, Loreto; Alswaid, Abdulrahman; Alrasheed, Shatha; et al.
Abstract : Background: Joubert syndrome (JS) is a ciliopathy characterised by a distinctive brain malformation (the 'molar tooth sign'), developmental delay, abnormal eye movements and abnormal breathing pattern. Retinal dystrophy, cystic kidney disease, liver fibrosis and polydactyly are variably present, resulting in significant phenotypic heterogeneity and overlap with other ciliopathies. JS is also genetically heterogeneous, resulting from mutations in 13 genes. These factors render clinical/molecular diagnosis and management challenging. CC2D2A mutations are a relatively common cause of JS and also cause Meckel syndrome. The clinical consequences of CC2D2A mutations in patients with JS have been incompletely reported. Methods: Subjects with JS from 209 families were evaluated to identify mutations in CC2D2A . Clinical and imaging features in subjects with CC2D2A mutations were compared with those in subjects without CC2D2A mutations and reports in the literature. Results: 10 novel CC2D2A mutations in 20 subjects were identified; a summary is provided of all published CC2D2A mutations. Subjects with CC2D2A -related JS were more likely to have ventriculomegaly (p<0.0001) and seizures (p=0.024) than subjects without CC2D2A mutations. No mutation-specific genotype–phenotype correlations could be identified, but the findings confirm the observation that mutations that cause CC2D2A -related JS are predicted to be less deleterious than mutations that cause CC2D2A -related Meckel syndrome. Missense variants in the coiled-coil and C2 domains, as well as the C-terminal region, identify these regions as important for the biological mechanisms underlying JS. Conclusions: CC2D2A testing should be prioritised in patients with JS and ventriculomegaly and/or seizures. Patients with CC2D2A -related JS should be monitored for hydrocephalus and seizures.